The Desiring Modes of Being Black—Essays in Literature and Critical Theory - (:unkn) unknown (My University, 2018)
The Desiring Modes of Being Black—Essays in Literature and Critical Theory includes essays on James Baldwin, Sigmund Freud, Ernest J. Gaines, Melvin Dixon, Essex Hemphill, Assotto Saint, and Rozena Maart. The metacritical reading they unfold interweaves African-American Culture, Fanonian and Caribbean Thought, South African Black Consciousness, French Theory, Psychoanalysis, and Gender and Queer Studies. A critique of theory through literature which celebrates the diversity of black being, The Desiring Modes of Being Black—Essays in Literature and Critical Theory explores how literature may contribute to unearth theoretical blind spots or shortcomings while reasserting the legitimacy of emotional turbulence in the controlled realm of reason that rationality claims to establish. This approach operates a critical shift by examining psychoanalytical texts from the literary perspective of black desiring subjectivities and experiences. In this combination of psychoanalysis and the politics of literary interpretation of black texts, what is at stake is to determine how contemporary African-American and diasporic literature and queer texts come to defy and possibly challenge the racial and sexual postulates of psychoanalysis and, in a broader perspective, any disciplinary perspective or theoretical system that intends to define race, gender, and sexuality.
Keywords: African Research